Lafadz Ijab Qabul Perspektif Fiqih As-Syafi’i - Arnisa Siregar; Ikhwanuddin Harahap; Adi syahputra sirait (Jurnal El-Thawalib, 2021)
Marriage is not just a written contract or usually spoken between the bride and groom. Ijab qabul is one of the pillars of marriage, there is ijab, namely lafadz spoken by the guardian of the prospective bride or her representative while qabul is lafadz spoken by the prospective groom. Then without the pillars in a marriage contract, the marriage is invalid. As happened in the process of the marriage contract in the city of Padangsidimpuan, the lafadz consent and qabul were not in accordance with the provisions of the Shari'a.The purpose of this thesis is to find out how the marriage registrar's perception of lafadz ijab qabul in the marriage process in the city of Padangsidimpuan.The conclusions obtained in this study are that the implementation of the ijab qabul lafadz in the procession of the marriage contract in the city of Padangsidimpuan lafadz qabul ijab as follows: the consent pronounced by the guardian must be in harmony with the qabul answered by the prospective groom. If the guardian of the prospective bride is her biological father in her consent, there is no need to say using binti, because it is clear in her consent that it is my biological daughter.